Uncertainty evaluation on the absolute phase error of digitizers. (February 2020) - Femine, Antonio Delle; Gallo, Daniele; Landi, Carmine; Luiso, Mario
In many engineering applications the phase angle of a signal is a key parameter. Especially when measuring small angles, the measurement accuracy is of a vital importance. Often, the absolute phase error of a digitizer, which is defined as the phase displacement between the digitized output and the input analog waveform and which represents a systematic measurement error, is neglected. Therefore, in this paper, a new measurement technique for the evaluation of this absolute phase error is discussed, along with a deep theoretical analysis on the uncertainty sources and how to handle them. The measurement technique is validated through a high accuracy experimental setup. Experimental tests demonstrate that even high accuracy digitizers can show non-linear behavior in the absolute phase errors.